Perancangan Sistem Penjualan Pada Toko Kembar Citayam Depok Berbasis Web - Hendrawan, Yoga; Fergina, Anggun (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research was motivated by observational data from researchers who were interested in the problems being faced by Toko Kembar Citayam. To overcome these problems, researchers conducted research at Toko Kembar Citayam which aimed to overcome and improve the quality of the store. The goal to be achieved in this study is to build a Web-based sales information system at the Depok Citayam Twin Store which is expected to facilitate to provide data information about the clarity of profit and loss and the effectiveness of subsequent sales. This research was conducted by the researcher himself who happened to work at the Depok Citayam Twin Store. Therefore, researchers have high ambitions to improve the quality of the store. The research design used is development (research and development / R D). With a case study approach at Toko Kembar Depok Citayam. Web-based sales information system development methods are made using prototype methods, and system development tools in the form of flowmaps, context diagrams, DFDs, and proposed database design tools in the form of ERDs. The author uses PHP, HTML, CSS, and Notepad for the database using MysQl